Evolution of professionals' careers upon graduation in STEM and occupational turnover over time: Patterns, diversity characteristics, career success, and self-employment - Katja Dlouhy; Ariane Froidevaux (Journal of Organizational Behavior, 2022)
While STEM occupational turnover constitutes a major concern for society given the importance of innovation and technology in today's global economy, it also represents an opportunity to achieve career sustainability for individuals. There is ample research on the reasons why students drop out from STEM education, but evidence on STEM professionals' career patterns and on correlates of occupational turnover after graduation is scarce. Drawing on the sustainable careers framework, the current study examines how STEM graduates' careers evolve over time, revealing diverse patterns of occupational turnover and the relationships of such career patterns with work diversity characteristics in terms of sex and ethnic minority status, career success, and self-employment. Using longitudinal data from 1512 STEM graduates over 10 years, results of an optimal matching analysis demonstrate six career patterns that can be distinguished into three continuity (STEM, part-STEM, non-STEM) and three change (hybrid, boomerang, dropout) sustainable career patterns. We find differences in sex, but not in ethnic minority status, across career patterns. Further, professionals who change from STEM occupations to non-STEM occupations show higher objective career success and are more often self-employed than those following a continuous STEM career pattern. Theoretical and practical implications of these findings are discussed.
Keywords: 650; career patterns; career success; minority; optimal matching analysis; self-employment; sex; STEM leaky pipeline; turnover